Beneficial Plant Microorganisms Affect the Endophytic Bacterial Communities of Durum Wheat Roots as Detected by Different Molecular Approaches - Agnolucci, Monica; Palla, Michela; Cristani, Caterina; Cavallo, Noemi; Giovannetti, Manuela; De Angelis, Maria; Gobbetti, Marco; Minervini, Fabio (Frontiers in Microbiology, 2019)
This study aimed at characterizing the endophytic bacterial communities living in durum wheat roots, as affected by wheat cultivar and inoculation of the arbuscular mycorrhizal fungus Funneliformis mosseae IMA1 and the wheat root endophytic bacterium Lactobacillus plantarum B.MD.R.A2. These microorganisms were inoculated, alone or in combination, in durum wheat (cultivars Odisseo and Saragolla). Non-inoculated plants of each cultivar represented the controls. Forty-three days after sowing, roots were deprived of the epiphytic microbiota and subjected to DNA extraction. The DNA was used as template in PCR-DGGE analysis of the 16S rRNA gene (variable region V3-V5) and 16S (region V1-V3) metagenetics. Odisseo and Saragolla root endophytic bacterial biotas differed for number of OTUs and composition. In detail, Pseudomonas was higher in Odisseo than in Saragolla. The inoculation of F. mosseae and L. plantarum increased the abundance of Pseudomonas, some Actinobacteria (e.g., Streptomyces, Microbacterium, two genera including several plant growth promoting strains) and Bacteroidetes in both cultivars. However, the endophytic bacterial biota of Saragolla roots inoculated just with lactobacilli did not differ from that of the control. The inoculation of Saragolla with F. mosseae, alone or in combination with lactobacilli, led to higher abundance of Rhodococcus, belonging to Actinobacteria and encompassing plant growth promoting strains. First, this work showed that F. mosseae and L. plantarum shape the endophytic bacterial biota of durum wheat roots. Abundance of some OTUs was affected by the microbial inoculation, depending on the cultivar. This result represents a starting point for exploitation of beneficial endophytes of wheat roots.